Micellar liquid chromatographic determination of sildenafil citrate in pharmaceutical formulations - Sujaritpun Jaipang (2018)
A simple, rapid, precise, accurate and selective micellar liquid chromatographic (MLC) method was developed and validated for the determination of sildenafil citrate in pharmaceutical formulations. Separation was achieved isocratically on an ACE 5 C18 - AR column (5 μm, 4.6 mm × 150 mm) utilizing a mobile phase of 8.2 mM SDS in acetate buffer (pH 4.0) at a flow rate of 0.5 mL min-1 with UV detection at 298 nm. All analyses were conducted at ambient temperature. Linear calibration curve was obtained over the concentration range of 125-500 μg mL-1, with a correlation coefficient (r2) greater than 0.999. The limits of detection and quantitation were found to be 35 μg mL-1 and 106 μg mL-1 respectively. The proposed method has been applied to the determination of sildenafil citrate in oral suspensions and tablets. Common excipients in formulations did not interfere. This method is suitable for routine analysis.